1996
DOI: 10.1111/j.1570-7458.1996.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neem allelochemicals on nutritional physiology of larval Spodoptera litura

Abstract: Neem allelochemicals azadirachtin, salannin, nimbinene and nimbin were administered to different larval instars of the tobacco armyworm, Spodoptera litura orally in artificial diet, topically or via injection. Nutritional analyses revealed strong antifeedant and growth regulatory effects of azadirachtin which were independent of each other. While salannin and nimbinene induced concentration dependent feeding deterrence only; nimbin was inactive to the 1000 ppm level against this insect species. One of the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…In fact, many limonoids can be antifeedants without having chronic toxicity (12), such as salannin and nimbinene in our study and limonin, epilimonol, nomilin, meliantriol, melianol, trichillins, pedonin, toonacilins, etc. in other studies (9,11,24). Azadirachtin is a strong antifeedant and growth regulator, and both activities are independent of each other, which is evident from the different ECI values in oral and topical treatments in H. armigera (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 80%
“…In fact, many limonoids can be antifeedants without having chronic toxicity (12), such as salannin and nimbinene in our study and limonin, epilimonol, nomilin, meliantriol, melianol, trichillins, pedonin, toonacilins, etc. in other studies (9,11,24). Azadirachtin is a strong antifeedant and growth regulator, and both activities are independent of each other, which is evident from the different ECI values in oral and topical treatments in H. armigera (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 80%
“…Many limonoids can be antifeedants without having chronic toxicity (Champagne et al 1992;Mendel et al 1993;Koul et al 1996;Aerts & Mordue 1997). Azadirachtin, however, is a strong antifeedant and growth regulatory allelochemical, where both activities are independent of each other.…”
Section: Discussionmentioning
confidence: 97%
“…This level of cypermethrin resistance is not surprising because this insecticide has been intensively used in this region. The variation in the toxicity of cypermethrin among the different Koul et al (1996), who reported that some allelochemicals exert strong growth regulatory effects against Spodoptera litura. Similarly, the resistant populations from Al-Ahsa and Al-Qatif also showed similar reductions in the ECD, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%